2014
DOI: 10.3109/00016357.2014.913192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of developmental odontogenic cysts in children and adolescents with emphasis on dentigerous cyst and odontogenic keratocyst (keratocystic odontogenic tumor)

Abstract: Adolescent patients with lesions located on the mandible would favor KCOT over dentigerous cyst. This study aids in better knowledge of the prevalence of developmental odontogenic cysts in a large pediatric population, and shows that a well-supported early diagnosis is indispensable for a more adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
2
7
0
3
Order By: Relevance
“…As formas de tratamento indicadas para os cistos são, basicamente, a enucleação (remoção total da lesão cística) e a descompressão (qualquer técnica que alivie a pressão dentro do cisto) 1,7,8 . Embora estas modalidades de tratamento possam ser utilizadas isoladamente, o tratamento mais adequado para grandes cistos é a associação de ambos os métodos, principalmente quando se deseja minimizar danos a estruturas importantes 8,13 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As formas de tratamento indicadas para os cistos são, basicamente, a enucleação (remoção total da lesão cística) e a descompressão (qualquer técnica que alivie a pressão dentro do cisto) 1,7,8 . Embora estas modalidades de tratamento possam ser utilizadas isoladamente, o tratamento mais adequado para grandes cistos é a associação de ambos os métodos, principalmente quando se deseja minimizar danos a estruturas importantes 8,13 .…”
Section: Discussionunclassified
“…Quando se deseja preservar os dentes, é imperativo que durante o procedimento cirúrgico se remova todo o epitélio do cisto sem, no entanto, remover os capuzes pericoronários e sem deslocar os elementos, para não causar traumas adicionais nem comprometimento ao aporte vascular 15 . Esta abordagem mais conservadora só é possível porque os cistos inflamatórios e o dentígero tem natureza benigna e baixas taxas de recidiva 7,8,15 . Neste contexto é imperativo saber qual a variante do cisto odontogênico está sendo tratada, pois algumas entidades, como o…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, this cyst may be associated with Nevoid Basal Cell Carcinoma Syndrome (NBCCS), or Gorlin-Goltz Syndrome, which is a rare autosomal dominant syndrome characterized primarily by multiple/recurrent OKC (present in at least 75% of patients), basal cell carcinomas and other clinical findings which usually appear during puberty or even during the first decade of life (5,9,10). The incidence of OKC is uncommon in patients from zero to 14 years, and few studies in literature have reported cases in non-syndromic children (11)(12)(13)(14)(15)(16). Based on that, the aim of this retrospective study was to review cases of OKC in children that attended an oral diagnostic center in Brazilian Northeast between 1986 and 2017 and to evaluate the presentation, radiological findings, and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most lesions are benign however, due to its high proliferation and recurrence rates as well as an aggressive behaviour, and considering that they may reach large dimensions and have a propensity for anterior and posterior growth oft en without clinical symptoms since clinically there is minor evident buccolingual expansion of the cortices, they are long covert and typically discovered during incidental x-ray examination. [2][3][4] The constantly rising incidence of orofacial tumours compel us to implement treatment modalities increasingly invasive and damaging since tumour lesions of the oral cavity are mostly surgically treated to properly eliminate and prevent further recurrences. In some malignant tumours, a more aggressive approach is elected resorting to ablative surgery in conjunction with radiotherapy and adjuvant chemotherapy, for localized and distant metastasis treatment.…”
Section: Introductionmentioning
confidence: 99%